2020
DOI: 10.1155/2020/4385286
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Kikuchi-Fujimoto Disease from Sub-Saharan Africa: An Important Mimic of Tuberculous Lymphadenitis

Abstract: Kikuchi-Fujimoto disease (KFD) is a rare form of painful lymphadenopathy, usually cervical, which is more common in Southeast Asia and rarely reported from Africa. Symptoms are usually nonspecific (fever, night sweats, etc.), and can mimic more common diseases such as tuberculosis (TB) in endemic areas. We report a case of a 29-year-old black African woman who was admitted with headache, neck pain, fever, and lymphadenopathy. She was found to have aseptic meningitis, eventually attributed to TB based on cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…KFD is a benign, self-limiting disease, and most patients do not need special treatment (3). Moreover, it has a low recurrence rate (3 to 4%), and only several fatal cases have been reported (3,5,18). In the retrospective analysis of 11 cases (Table 2: cases 28 and 32-41) of KFD patients with meningitis, Sato et al found that meningitis symptoms would spontaneously recede within 2-6 weeks without special treatment (26).…”
Section: Discussionmentioning
confidence: 99%
“…KFD is a benign, self-limiting disease, and most patients do not need special treatment (3). Moreover, it has a low recurrence rate (3 to 4%), and only several fatal cases have been reported (3,5,18). In the retrospective analysis of 11 cases (Table 2: cases 28 and 32-41) of KFD patients with meningitis, Sato et al found that meningitis symptoms would spontaneously recede within 2-6 weeks without special treatment (26).…”
Section: Discussionmentioning
confidence: 99%
“…The first is viral infection and the second theory explains the appearance of KFD in the course of autoimmune disease. 2,6,7 The confirmation of the 'viral disease' theory in the course of KFD. The large number of histiocytes and CD8 + lymphocytes in the affected lymph nodes seems to confirm the viral infection etiology of KFD.…”
Section: Etiologymentioning
confidence: 99%
“…In most cases, Hashimoto's disease manifested itself at the same time as KFD. 3,6 KFD may cooccur before, during or after the onset of SLE. Therefore, the diagnosis of KFD requires longterm monitoring for the development of SLE.…”
Section: Epidemiology and Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations